2020
DOI: 10.1016/j.jbo.2020.100304
|View full text |Cite
|
Sign up to set email alerts
|

ceRNA network development and tumour-infiltrating immune cell analysis of metastatic breast cancer to bone

Abstract: Highlights There were significant differences in lncRNAs, 18 miRNAs, and 20 mRNAs between breast cancer with and without bone metastasis. JGB3, CAMGV, PTPRZ1, and FBN3 mRNA were related to prognosis of patients with metastatic breast cancer of bone. The proportions of plasma cells and follicular helper T cells were significantly higher in breast cancer with bone metastasis. The model composed of activated mast cells, gamma delta T cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…After diagnosis, the physical, mental, and social health-related quality of life (HRQoL) of patients with BC significantly declines (42). Increasing evidence indicated that ceRNAs and dysregulation of the immune system are involved in the progression of human tumors (43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…After diagnosis, the physical, mental, and social health-related quality of life (HRQoL) of patients with BC significantly declines (42). Increasing evidence indicated that ceRNAs and dysregulation of the immune system are involved in the progression of human tumors (43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…The CIBERSORT algorithm was used to estimate the abundance of 22 immune cell subtypes according to the RNA-seq count data [ 26 ]. The associations between immune cell types and prognosis were investigated by univariate Cox regression, LASSO regression, and multivariate Cox regression.…”
Section: Methodsmentioning
confidence: 99%
“…A hazard ratio ðHRÞ > 1 and P < 0:05 were considered to indicate unfavorable prognostic factors, whereas HR < 1 and P < 0:05 indicated favorable prognostic factors [25]. The CIBERSORT algorithm was used to estimate the abundance of 22 immune cell subtypes according to the RNAseq count data [26]. The associations between immune cell types and prognosis were investigated by univariate Cox regression, LASSO regression, and multivariate Cox regression.…”
Section: Construction and Confirmation Of Cerna-relatedmentioning
confidence: 99%
“…Cox regression analysis was further applied to analyze the relationship of risk score prognosis of PAAD patients. Finally, the “rms” package was used to draw a nomogram for predicting 1-, 3-, and 5-year OS of PAAD patients in modeling cohort ( Kim et al, 2018 ; Liu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%